Complex pattern formation in solutions of protein and mixed salts using dehydrating sessile droplets - Pathak B.; Christy J.; Sefiane K.; Gozuacik D. (My University, 2025)
A sessile droplet of a complex fluid exhibits several stages of drying leading to the formation of a final pattern on the substrate. We report such pattern formation in dehydrating droplets of protein (BSA) and salts (MgCl2 and KCl) at various concentrations of the two components (protein and salts) as part of a parametric study for the understanding of complex patterns of dehydrating biofluid droplets (blood and urine), which will eventually be used for diagnosis of bladder cancer. The exact analysis of the biofluid patterns will require a rigorous parametric study; however, the current work provides an initial understanding of the effect of the basic components present in a biofluid droplet. Arrangement of the protein and the salts, due to evaporation, leads to the formation of some very distinctive final structures at the end of the droplet lifetime. Furthermore, these structures can be manipulated by varying the initial ratio of the two components in the solution. MgCl2 forms chains of crystals beyond a threshold initial concentration of protein (>3 wt %). However, the formation of such a crystal is also limited by the maximum concentration of the salt initially present in the droplet (≤1 wt %). On the other hand, KCl forms dendritic and rectangular crystals in the presence of BSA. The formation of these crystals also depends on the relative concentration of salt and protein in the droplet. We also investigated the dried-out patterns in dehydrating droplets of mixed salts (MgCl2 + KCl) and protein. The patterns can be tuned from a continuous dendritic structure to a snow-flake type structure just by altering the initial ratio of the two salts in the mixture, keeping all other parameters constant. Copyright © 2020 American Chemical Society.